BIM‐Based Urban Building Facility Information Management System - Guo, Cheng; Ding, Yang; Guo, Zhen‐Zhen; Zhou, Shuang‐Xi; Chu, Tian‐Yun (Engineering reports (Hoboken, N.J.), 2025)
ABSTRACT Traditional facility management in the construction industry faces critical challenges, including fragmented lifecycle data, inefficient manual operations, and disconnection between design, construction, and operation phases, which severely hinder data traceability and management efficiency. To address these issues, this study develops a BIM‐based integrated data analysis and management system for building facility operation and maintenance (OM) through a structured methodology. The system development adopts the Spring + SpringMVC + MyBatis (SSM) framework for web application architecture, combined with lightweight BIM technology to realize model embedding and real‐time data interaction. Key technical steps include: (1) lightweight processing of BIM models via the BIMface engine to enable integration with management systems; (2) designing six core functional modules to cover full‐lifecycle needs; (3) establishing a traceable data chain linking design parameters, construction records, and operational data through standardized data mapping. The platform supports multi‐phase applications through targeted mechanisms: In the planning and design phase, it integrates early design requirements with maintenance data via visualized analysis to optimize schemes. During post‐construction operation, predictive analytics on spatial and infrastructure data enhance utilization efficiency. For full‐lifecycle management, real‐time monitoring of equipment operations is achieved by integrating sensor data with lightweight BIM models, while a closed‐loop management mechanism tracks facility service lifespans from design to decommissioning. This paper proposes a BIM‐based integrated data analysis and management system platform for building facility operation and maintenance (OM). The developed platform demonstrates comprehensive applicability throughout the entire lifecycle of construction projects. During the initial planning and design phase, the system enables traceable data analysis for early‐stage design requirements while facilitating information integration with subsequent maintenance phases, thereby effectively optimizing architectural planning and design schemes. In the post‐construction operational phase, the platform enhances spatial utilization efficiency of building facilities through predictive data analytics for OM space planning and infrastructure configuration. The system's visualized data analysis and optimized management modules prove particularly valuable during complex construction OM stages, significantly reducing cyclical project modifications through proactive data processing capabilities. For the full lifecycle management phase, the platform implements real‐time monitoring of equipment operation and post‐construction maintenance services. It establishes a traceable management mechanism covering the complete service lifespan of building facilities and equipment, achieving seamless integration of O&M data flow from initial design through final decommissioning.